The complete Star Wars trilogy scrapbook : an out of this world guide to Star Wars, The Empire strikes back, and Return of the Jedi - Vaz, Mark Cotta (New York : Scholastic, 1997)
"Packed with over 100 pictures, this book contains vital information on all the characters, planets, weapons, heroes, villains, aliens, and droids of this fascinating world." -- back cover.
1040
Keywords: Star wars (Motion picture); Empire strikes back (Motion picture); Return of the Jedi (Motion picture)